1991
DOI: 10.1002/ijc.2910480412
|View full text |Cite
|
Sign up to set email alerts
|

Expression of collagenase‐related metalloproteinase genes in human lung or head and neck tumours

Abstract: We address the question as to whether increased metalloproteinase production might be related to the high regional recurrence rate of some carcinomas, and particularly head and neck squamous-cell carcinomas (SCC). Northern blot of total RNA prepared from 26 lung carcinomas, 107 head and neck carcinoma samples and corresponding normal tissue samples demonstrates the frequent and sometimes concomitant over-expression of the 2 stromelysin genes, the type-I collagenase gene and the pump-I gene in the head and neck… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
0
3

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(110 citation statements)
references
References 25 publications
5
102
0
3
Order By: Relevance
“…Our data also indicate that MMP-10 expression profiling may be of prognostic significance. Interestingly, MMP-10 overexpression has also been observed in squamous cell carcinomas of the head and neck (Muller et al, 1991;O-Charoenrat et al, 2001), oral cavity (Impola et al, 2004) and esophagus (Mathew et al, 2002). These tumor types harbor frequent chromosome 3q26 and PRKCI amplification (Pimkhaokham et al, 2000;Imoto et al, 2001;Snaddon et al, 2001;Osada and Takahashi, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Our data also indicate that MMP-10 expression profiling may be of prognostic significance. Interestingly, MMP-10 overexpression has also been observed in squamous cell carcinomas of the head and neck (Muller et al, 1991;O-Charoenrat et al, 2001), oral cavity (Impola et al, 2004) and esophagus (Mathew et al, 2002). These tumor types harbor frequent chromosome 3q26 and PRKCI amplification (Pimkhaokham et al, 2000;Imoto et al, 2001;Snaddon et al, 2001;Osada and Takahashi, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Recent in vivo studies have indicated that cancer cells are able to induce production of proteases by neighbouring stromal cells (Hewitt et al, 1991;Muller et al, 1991;Polette et al, 1991;Borchers et al, 1994). The inability to identify a specific MMP gene or genes common to all cancers supports the probability that progression may be affected by quantitative changes in levels of expression of one or more MMPs, differential expression of TIMP inhibitors, or qualitative changes in the specific genes expressed.…”
Section: Northern Blot Analysis Of Gelatinase a And B Transcriptsmentioning
confidence: 99%
“…Since ®brillar collagens are the most abundant structural components of human connective tissues, the ability to degrade them is crucial for invasion and metastasizing of neoplastic cells. Expression of MMP-1 has been observed in lung carcinomas (Urbanski et al, 1992;Wernert et al, 1994), squamous cell carcinomas of the head and neck (Polette et al, 1991;Muller et al, 1991;Gray et al, 1992), and in colorectal tumors, in which expression of MMP-1 correlates with poor prognosis (Hewitt et al, 1991;Murray et al, 1996). In these tumors, stromal cells appear to be responsible for MMP-1 production, indicating importance of crosstalk between tumor and stromal cells in tumor cell invasion (for review see Stetler-Stevenson et al, 1993;Wernert et al, 1994;Bolon et al, 1995).…”
Section: Introductionmentioning
confidence: 99%